Solvatochromic behavior on the absorption, transmittance and emission spectra for some organic dyes as active media - Hadi, Alaa N.; Abbas, Talib M. (Edelweiss Applied Science and Technology, 2024)
This research examines the absorption and emission (fluorescence) spectra of several solutions containing mixtures of organic dyes dissolved in ethanol, analyzed at three distinct concentrations (0.1, 0.2, 0.3 mM) for each mixture. Two organic dyes were combined: (Fluorescein + Eosin), (Fluorescein + Methyl Orange), and (Malachite Green + Azure B), each with a defined weight. As the concentration of these dye mixtures decreases, so do the absorbance values and an increase in transmittance values and vice versa. This is consistent with the Beer-Lambert law, which also leads to a decrease in the values of all linear optical properties. The fluorescence spectra were obtained via a fluorescence spectrometer. The fluorescence lifespan and quantum efficiency of fluorescence were computed to derive a combination of dyes with elevated quantum efficiency suitable for use as active media in dye lasers.